Information at the Bibliothèque Nationale de France - Renoult, Daniel (LIBER Quarterly: The Journal of the Association of European Research Libraries, 1999)
Following the opening of the general public level in december 1996, the French National Library will open the research level in october 1998. This will coincide with the inauguration of the new integrated information system which is designed to manage all functions of a large national library.